Lake sediment records of deglaciation and post-glacial paleoenvironmental conditions, northeast Pennsylvania, USA - Matthew S. Finkenbinder; Timothy P. Lane; Kathryn R. Adamson; Bruce P. Finney; Mark B. Abbott; Alistair J. Monteath; Adam Ianno; Cassandra N. Papp; Angus F. Fortune; Michael J. Delpais; Megan E. Novak; Angelica Y. Delgado Rodriguez; et al. (Quaternary Science Reviews, 2026)

Shrimp (sub-)national traceability and retail fraud detection using stable isotopes and multi-element profiling - V. Deklerck; R.P. Davis; A. Rodriguez-Zunino; S. Khongtanakrittakorn; S. Hofem; J. Jungkeit; A. Leyton; M. Osorto-Nuñez; C. Podmore; L. Prior; C.C. Smith; B. Soule; et al. (Food Control, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Hypertrophic cardiomyopathy-linked Tnnc1 variants are associated with distinct myopathic changes in slow skeletal muscle of mice - Sonu Patel; Gabriel Leite da Silva Santos; Jaelynn Florence; Aida Rahimi Kahmini; Yun Shi; Michelle Rodriguez Garcia; Bradley S. Gordon; P. Bryant Chase; Christopher Solís; Orlando Laitano; J. Renato Pinto; Michelle S. Parvatiyar (Journal of Muscle Research and Cell Motility, 2026)

Low-dose inorganic arsenic exposure reprograms macrophages differentiation and function toward tumor-promoting phenotypes - Emily J. Illingworth; Sylvia S. Sanchez; Kristal A. Rychlik; Andre Kleensang; Jason Laird; Gabriel A. Lopez-Cecetaite; M. Carolina Rodriguez Steube; Aakriti Mathur; Pritam Sadhukhan; Daniel A. Medina-Cleghorn; Daniel Nomura; Martyn T. Smith; et al. (Environmental Research, 2026)

Confirmed Outbreaks of Streptococcosis Caused by Streptococcus agalactiae Serotype Ia in Nile Tilapia Culture From Campeche, Mexico - R. A. Avila‐Castillo; R. E. del Rio‐Rodriguez; S. A. Soto‐Rodriguez; J. Navarro‐Flores; A. D. Cu‐Escamilla; F. I. Marrujo‐Lopez; K. G. Aguilar‐Rendon; M. I. Gomez‐Solano (Journal of Fish Diseases, 2026)
Streptococcus agalactiae was confirmed as the etiologic agent of streptococcosis in Nile tilapia ( Oreochromis niloticus ) from Campeche, Mexico, during a cross‐sectional investigation of eight semi‐intensive farms (2021–2022) that yielded virulent strains in a challenge assay. Standard bacteriology, histopathology, API‐20 Strep phenotyping, one‐step PCR, and real‐time PCR confirmed S. agalactiae in five farms (62.5%). Gross and histological lesions were characterised by mid‐axial and peduncular muscle abscesses, extensive myonecrosis, granuloma formation, polyserositis, and occasional suppurative meningitis. Experimental infections fulfilled Koch's postulates. Juveniles of O. niloticus (20 g) infected with strain ASG‐2290 at 10 6 CFU/mL produced 53% mortality at 96 h. Whole‐genome sequencing of the strains ASG‐2290 and ASG‐2292 identified them as S. agalactiae Ia, marking the first report of this serotype isolated from farmed tilapia in Mexico. Frequent interstate fry movements are likely to be a risk factor for pathogen dissemination. These findings document the geographic expansion of pathogenic S. agalactiae into the Yucatan Peninsula, underscoring the need for strengthened surveillance, biosecurity, and diagnostic capacity to mitigate economic losses in Mexican tilapia aquaculture. Considering that tilapia aquaculture is carried out all year‐round in the Yucatan Peninsula, the implications of these findings are of major concern.

Transcriptomic response of Acropora cervicornis following transplantation to a marginal, nearshore environment - Allyson DeMerlis; Colin Foord; Dalton J. Hesley; Richard F. Karp; Lys M. Isma; Natalia Andrade-Rodriguez; Kevin H. Wong; Michael S. Studivan; Mike Jankulak; Andrew C. Baker; Diego Lirman; Nikki Traylor-Knowles; et al. (Frontiers in Marine Science, 2026)
As reef-building coral cover has declined worldwide, coral restoration has become a widespread response towards repopulating degraded reefs. In-situ nurseries have provided refugia for the regrowth of several coral species, yet long-term success following outplanting remains highly variable, particularly when corals are introduced into novel or marginal environments. Additionally, while growth and survivorship are commonly used to evaluate restoration success, molecular responses may also provide critical insights into the capacity of corals to acclimatize following transplantation. Here, we examined host and algal symbiont gene expression in the critically endangered reef-building coral Acropora cervicornis following transplantation from an offshore nursery in Key Biscayne, Florida to a nearshore, urbanized habitat in the Port of Miami, Florida. Three nursery-propagated genotypes were outplanted in June 2021 and sampled after four months at both sites for transcriptomic analysis ( n =12 after quality filtering). Transplanted corals exhibited significant shifts in host gene expression relative to nursery controls, with 961 host and symbiont genes significantly upregulated and 165 significantly downregulated. Upregulated host genes were predominantly associated with the environmental stress response, including heat shock proteins, unfolded protein binding, apoptotic processes, detoxification pathways, and innate immune signaling. Weighted gene co-expression network analysis identified two host modules positively associated with the nearshore outplant site and were enriched for pathways related to protein folding, immune activity, and cellular reorganization. These results demonstrate that A. cervicornis outplanted to a nearshore, urbanized environment exhibits sustained activation of stress- and immune-related molecular pathways months after transplantation, which is consistent with a stress-response profile that may reflect ongoing acclimatization. Integrating molecular diagnostics with environmental monitoring may refine genotype and site selection to enhance restoration outcomes.

Modelling primary production: multitude of theories, or multitude of languages? - Jozef Skákala; Shubha Sathyendranath; Yuri Artioli; Deep S. Banerjee; Heather Bouman; Robert J. W. Brewin; Momme Butenschön; Stefano Ciavatta; Stephanie Dutkiewicz; Yanna Fidai; David Ford; Grinson George; et al. (Ocean Science, 2026)
Marine primary production, converting approximately 50 Gt of inorganic carbon into organic carbon per year, is an important component of the global carbon cycle, and a major determinant of past, present and future climate. Large-scale, long-term estimates of marine primary production rely primarily on two types of models: satellite-based models that make extensive use of remote-sensing data, and ecosystem models providing numerical simulation of ecological processes embedded in general ocean circulation models. Intercomparison exercises of model outputs (both within and across the two model types) have consistently revealed high discrepancies between estimated global ocean primary production, including divergent magnitudes and even opposite trends. Model-observation comparisons are also complex, because paucity of data, differences in measurement techniques, and evolving methodologies could all lead to difficulties with the interpretation of results. These uncertainties limit the applications of primary production models (both satellite-based and ecosystem), especially in the climate context, where an important question is whether climate change will drive significant future changes in regional or global primary production. Both satellite-based and ecosystem models rely on a range of fixed model parameters, whose values need to be carefully estimated and tested. In this paper, we suggest that such model parameters represent an underappreciated but important source of inter-model differences. With the proliferation of both satellite and in situ observations of relevant variables at global scales, and the availability of powerful statistical tools such as data assimilation and machine learning, we argue that time is right to systematically examine model parameters, gaining both better insights into parameter values and how those values might vary in space and time. We argue that such spatio-temporal parameter variability can be theoretically justified for ecosystem models with complexity similar to those commonly used within Earth System Models (ESMs) in climate studies. The spatially and temporally varying parameter values could serve to unify models that are structurally different. An important aspect of this unification could be the ability to infer the spatio-temporal variability of parameters in the less complex models from the emergent behaviour of the more complex ones. This could include ecosystem model simulations of nutrients, temperature, phytoplankton classes, or vertical distributions informing satellite-based models. We conclude that better understanding of model parameter roles and integration (or inter-calibration) of different types of models could reduce discrepancies among the primary production models and improve the reliability of marine primary production projections.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Petiole Nitrate Analysis: A Diagnostic Method for Optimizing Nitrogen Management in Potato - C. M. Giletto; W. Carciochi; S. E. Silva; M. N. Cassino; S. Rodriguez; J. C. Laborde Amador; E. C. Zamuner; N. I. Reussi Calvo (Potato Research, 2026)

Contributions to the knowledge of DNA barcodes and diversity of intertidal and shallow-water mollusks in the Beagle Channel - L. D. Chiberry; J. Sánchez; V. M. Núñez; S. Rodriguez; M. Pellegrino; S. Poljak (Polar Biology, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Impacts of Diverse Stakeholder Participation on Fisheries Management - Sangeeta Mangubhai; S. L. Smith; Z. Davis; N. Koedyker; J. Augustyn; D. Durholtz; S. Fulton; Harlisa; M. T. Hidayat; L. Hiriart-Bertrand; M. Khazali; E. Litsinger; et al. (Coastal Management, 2026)

Use of shotgun immunoproteomics for the development of protein vaccines against Edwardsiella piscicida - Kim L. Jacobsen; Matt J. Griffin; Brett S. Phinney; Michelle Salemi; Zeinab Yazdi; Sujita Balami; Caitlin E. Older; Cynthia C. Ware; Fernando Y. Yamamoto; Noor-ul Huda; Tania Rodriguez-Ramos; Brian Dixon; et al. (Fish & Shellfish Immunology, 2026)

Associations between exposure to metals, chlorinated pesticides, and PCBs and differential leukocyte profiles in Flemish adolescents - Fen Zhang; Lützen Portengen; Hamid Y. Hassen; Laura Rodriguez Martin; Madeline Carsique; Amélie Crépet; Jasper Engel; Jacob Van Klaveren; Nicolas Van Larebeke; Willy Baeyens; Stefaan De Henauw; Tim S. Nawrot; et al. (Environmental Research, 2026)

A Simple Model to Estimate the Economic Optimum Nitrogen Rate in Potato Using Vegetation Indices - Claudia M. Giletto; W. D. Carciochi; F. M. Inchauspe; S. E. Silva; M. N. Cassino; V. Ortega; S. Rodriguez; J. C. Laborde Amador; N. Reussi Calvo (Potato Research, 2025)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Discovery of Latissimia ningalooensis: a new invasive soft coral species in Puerto Rico - Daniel A. Toledo-Rodriguez; Catherine S. McFadden; Nilda M. Jimenez Marrero; J. David Muñoz-Maravilla; Alex J. Veglia; Ernesto Weil; Nikolaos V. Schizas (Biological Invasions, 2025)

The key mechanisms associated with the survival of Gulf toadfish, Opsanus beta , when in severe hypoxia - Anastasiya Plotnikova; Isabelle R. Nelson; Shara Y. Sookhoo; Jacob M. Belkin; Vanessa P. Lima; Ross D. Bronfman Bunch; Athena M. Santomero; Sophia A. Santomero; Emily C. Rodriguez; Jayda K. Rodriguez; Kathleen M. Davis; Amanda J. Kaplan; et al. (Journal of Fish Biology, 2025)
Florida's shallow seagrass beds experience daily diurnal fluctuations in environmental oxygen, leading to hypoxic episodes (PO 2 −1 , ~6 kPa) that have increased in frequency and intensity in recent decades. The native Gulf toadfish ( Opsanus beta ) have been shown to employ a suite of adaptive cardiovascular, ventilatory and metabolic adjustments to survive moderate hypoxia, but little is known of the mechanisms used to survive severe hypoxia. The objective of this study was to characterize the acute response of Gulf toadfish to severe hypoxia ( 2 ~0.4 kPa for 3 h followed by 1 h recovery). Heart rate, pulse pressure, caudal arterial blood pressure, ventilation frequency and ventilation amplitude were monitored and blood samples were taken from both groups and analysed for pH, glucose, lactate and other endpoints. Hypoxia‐exposed fish experienced a statistically significant 70% decrease in heart rate and a 32% decrease in ventilation frequency during hypoxia exposure. Moreover, plasma glucose concentrations increased 5‐fold and plasma lactate concentrations increased 6‐fold, with a minimal reduction in pH. Our findings support our hypothesis that Gulf toadfish are highly hypoxia tolerant and survive severe hypoxia by reducing energy expenditure and switching to anaerobic metabolism. It is important to understand how the Gulf toadfish deal with severe hypoxia due to the increasing prevalence of severe hypoxia in its natural environment.

Optimistic climate mitigation scenario halves projected range loss in a neotropical dolphin - Rodrigo Tardin; Guilherme Maricato; Jeremy J. Kiszka; Mauricio Cantor; Israel Maciel; Gabriel Melo-Santos; Laura May-Collado; Ana Carolina Meirelles; Maria Isabel C. Gonçalves; Fábio G. Daura-Jorge; Renata S. Sousa-Lima; Yvonnick Le Pendu; et al. (Ocean & Coastal Management, 2025)

A comparison of the life history and distribution of vermilion rockfish (Sebastes miniatus) and its cryptic pair, sunset rockfish (S. crocotulus) along the Pacific Coast - John H. Harms; Anita Wray; John R. Hyde; Gary C. Longo; Jennifer A. Hempelmann; Anna E. Elz; R. Matthew Barnhart; James A. Benante; Aaron C. Chappell; Peter H. Frey; Colin L. Jones; Betty Kamikawa; et al. (Fisheries Research, 2025)

Development of a biotechnological process for the production of recombinant canine interferon-alpha using the baculovirus-insect cell and larvae system - Maria S. Rodriguez; Ignacio Smith; Marcela S. Villaverde; Joaquin M. Birenbaum; Joaquin Poodts; Federico J. Wolman; Alexandra M. Targovnik; Maria V. Miranda (Biotechnology Letters, 2025)

Multi-wavelength internal standardization using inductively coupled plasma optical emission spectrometry - Reagan Elia; Thomas J. Johnston; Alberto D. Figueroa; Emily M. Curbow; Mayra S. Gonzalez Guzman; Leah C. Rodriguez Cabrera; Marisa M. Morcom; Willis B. Jones (Analytica Chimica Acta, 2025)

Characterization of agr-like Loci in Lactiplantibacillus plantarum and L. paraplantarum and Their Role in Quorum Sensing and Virulence Inhibition of Staphylococcus aureus - Weizhe Wang; Ifigeneia Kyrkou; Martin S. Bojer; Dina Kalloubi; Abdul Jabbar Kali; Miguel Alena-Rodriguez; Jørgen J. Leisner; Stephanie Fulaz; Hanne Ingmer (Probiotics and Antimicrobial Proteins, 2025)
The pathogenicity of Staphylococcus aureus is largely regulated by the agr quorum sensing (QS) system encoded by agrBDCA , which coordinates virulence factor production through secretion and sensing of auto-inducing peptides (AIPs). agr -like systems are also present in coagulase-negative staphylococci, and several of these encode AIPs that inhibit S. aureus QS. In lactic acid bacteria, a similar locus was previously identified in Lactiplantibacillus plantarum WCSF1 termed lamBDCA . Here, we characterized the lamBDCA locus in L. plantarum LMG 13556 and L. paraplantarum CIRM-BIA 1870, and explored the effects on S. aureus QS. Notably, we found that co-cultivation with L. paraplantarum significantly inhibits S. aureus QS and hemolysin production, while less so for L. plantarum . The inhibition by L. paraplantarum was lost upon disruption of its lamBDCA locus, suggesting that the L. paraplantarum AIP mediates cross-species interference with S. aureus agr activation. Transcriptomic analysis revealed that lamBDCA in L. paraplantarum controls the expression of genes belonging to various functional categories, including stress response and metabolism. The latter includes genes encoding riboflavin (B2 vitamin) biosynthesis, which enabled the growth of the L. paraplantarum lamB mutant in the presence of roseoflavin, a toxic riboflavin analogue. Collectively, our results show that L. paraplantarum CIRM-BIA 1870 interferes with S. aureus virulence gene expression through QS suppression, and they implicate QS in the probiotic properties of L. paraplantarum .

Shadows over Caribbean reefs: occurrence of a new invasive soft coral species, Xenia umbellata, in southwest Puerto Rico - Daniel A. Toledo-Rodriguez; Alex J. Veglia; Nilda M. Jimenez Marrero; Joyce M. Gomez-Samot; Catherine S. McFadden; Ernesto Weil; Nikolaos V. Schizas (Coral Reefs, 2025)

Correction: Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Lignin hydrotreatment to aromatics products on metallic phosphides carbon-based catalysts produced from lignin - M. García-Rollán; S. Bertran-Llorens; M.A. Palazzolo; P.J. Deuss; H.J. Heeres; R. Ruiz-Rosas; J.M. Rosas; J. Rodriguez-Mirasol; T. Cordero (Fuel, 2025)

Understanding osmoregulation, cryoprotectant toxicity, and cold tolerance in sea urchin eggs: Implications for cryopreservation - S. Campos; Uxía Rodriguez; J. Troncoso; E. Paredes (Cryobiology, 2025)

Biomechanical and Compositional Changes in the Murine Uterus with Age - Mari J. E. Domingo; Triniti N. Vanoven; Raffaella De Vita; Maria E. Florian Rodriguez; Kristin S. Miller; Isaac J. Pence (Annals of Biomedical Engineering, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Parasite diversity in sea turtles of the temperate SW Atlantic: a bridge between systematics and ecology - E. O. Palumbo; C. K. Álvarez; S. Rodriguez-Heredia; A. Rosenthal; M. Vassallo; I. M. Bruno; J. Loureiro; L. Diaz; A. Faiella; M. R. Werneck; J. I. Diaz; V. González Carman (Marine Biology, 2025)

Temperature Drives Seagrass Recovery Across the Western North Atlantic - Fee O. H. Smulders; Justin E. Campbell; Andrew H. Altieri; Anna R. Armitage; Elisabeth S. Bakker; Savanna C. Barry; S. Tatiana Becker; Enrique Bethel; James G. Douglass; Hannah J. van Duijnhoven; Jimmy de Fouw; Thomas K. Frazer; et al. (Global Change Biology, 2025)
Climate‐driven shifts in herbivores, temperature, and nutrient runoff threaten coastal ecosystem resilience. However, ecological resilience, particularly for foundation species, remains poorly understood due to the scarcity of field experiments conducted across appropriate spatial and temporal scales that investigate multiple stressors. This study evaluates the resilience of a widespread tropical marine plant (turtlegrass) to disturbances across its geographic range and examines how environmental gradients in (a)biotic factors influence recovery. We assessed turtlegrass resilience by following recovery rates for a year after a simulated pulse disturbance (complete above‐ and belowground biomass removal). Contrary to studies in temperate areas, higher temperature generally enhanced seagrass recovery. While nutrients had minimal individual effects, they reduced aboveground recovery when combined with high levels of herbivore grazing (meso and megaherbivore). Belowground recovery was also affected by combined high levels of nutrients and grazing (megaherbivores only). Light availability had minimal effects. Our results suggest that the resilience of some tropical species, particularly in cooler subtropical waters, may initially benefit from warming. However, continuing shifts in nutrient supply and changes in grazing pressure may ultimately serve to compromise seagrass recovery.

Perceptions and Attitudes of Drinking Water Supply Systems Staff Towards Climate Change Adaptation for Drinking Water Quality Management - S. M. Cynthia Compaoré; Ianis Delpla; Sonja Behmel; Manuel J. Rodriguez (Environmental Processes, 2025)

The use of lichens and mosses as sentinel organisms for the determination of the airborne organic pollution in Western Pyrenees: The case of the Irati forest - J. Bustamante; A. Gredilla; O. Liñero; D. Amouroux; D. Elustondo; J.M. Santamaría; A. Rodriguez-Iruretagoiena; S. Fdez-Ortiz de Vallejuelo; G. Arana; A. de Diego (Atmospheric Pollution Research, 2025)

Exploring the effects of cellulose sources on silver reduction and the bacterial removal of nanocellulose-based hydrogel beads - Diego Gomez-Maldonado; Brieanne R. Dickson; Gabriel Au; Michael J. Bortner; Mi Li; Eduardo Espinosa; Alejandro Rodriguez; Brendan Higgins; Maria S. Peresin (Carbohydrate Polymers, 2025)

A review of the venom microbiome and its utility in ecology and evolution including future directions for emerging research - Marina E. De León; Eduardo G. P. Fox; Sara Dunaj; Ronald A. Jenner; Carl N. Keiser; Jason Macrander; Samantha A. Nixon; Clarissa J. Nobile; Daniel Petras; Eduardo Rodriguez-Roman; Anthony J. Saviola; Steven A. Trim; et al. (Symbiosis, 2025)

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

A multi-technique approach to unveil the composition and fabrication of a pre-Roman glass masterpiece: a double-faced human-head shape polychrome glass pendant (2nd -1st c. BC) - S. Barroso-Solares; E. Estalayo; J. Aramendia; E. Rodriguez-Gutierrez; C. Sanz-Minguez; A. C. Prieto; J. M. Madariaga; J. Pinto (Archaeological and Anthropological Sciences, 2024)
Pre-Roman glass craftsmanship reached its summit with the development of complex polychrome glass beads, being the Phoenician glass pendants the most exquisite and elaborate example. The uniqueness and complexity of such findings could reveal key information for the understanding of the production and trade of glass pieces at that age. However, these findings have practically never been studied from a physic-chemical perspective. In this work, a remarkable polychrome glass pendant (2nd -1st c. BC) found at the archaeological site of Pintia (Padilla de Duero, Valladolid, Spain) is studied by a multi-analytical non-destructive approach, employing X-ray tomography to understand its fabrication procedure, as well as X-ray fluorescence (XRF) and Raman spectroscopy, both employed in microscopic mode, to determine the composition of each glass employed in its fabrication. The outstanding preservation state and well-defined archaeological context of this glass pendant offered a unique opportunity to expand the understanding of pre-Roman glass pieces, while the combination of the experimental techniques employed provided the first complete and detailed study of a Phoenician glass pendant. The fabrication procedure of the pendant has been identified step-by-step, showing evidence of the use of pre-made pieces for the eyes, as well as hints of its fabrication in a secondary workshop. Moreover, the microchemical analysis of the vividly colored glasses by XRF and Raman spectroscopy revealed a composition compatible with the use of natron as fluxing agent, typical of Phoenician glass, the presence of surface alterations corresponding to carbonatation processes, as well as the nature of the employed chromophores or pigments: Mn, Cu, and Co for the blue, Fe-S for the black, CaSb 2 O 7 and CaSb 2 O 7 + TiO 2 for two diverse white glasses, and a pyrochloric triple oxide (Pb 2 Sb 2 − x Sn x O 7−x/2 ) and lead oxides for the yellow. Remarkably, the use of pyrochloric triple oxides as yellow pigments has scarcely been previously reported at that age. Finally, the identification by Raman spectroscopy of CaSb 2 O 7 and the β-phase of CaSiO 3 , as well as the Raman spectra features of the glass matrix corresponding to the blue glass, indicated maximum firing temperatures below 1100 °C.

No Effect of Breakfast Consumption Observed for Afternoon Resistance Training Performance in Habitual Breakfast Consumers and Nonconsumers: A Randomized Crossover Trial - Matthew T. Stratton; Madelin R. Siedler; Christian Rodriguez; Patrick S. Harty; Jake R. Boykin; Dale S. Keith; Jacob J. Green; Sarah J. White; Ethan Tinoco; Brielle DeHaven; Trisha A. VanDusseldorp; Grant M. Tinsley (Journal of the Academy of Nutrition and Dietetics, 2024)

Impact of a water restriction on the summer climatic benefits of trees inside an outdoor street canyon scale model - J. Thierry; S. Herpin; R. Levi; D. Canonne; S. Demotes-Mainard; P. Cannavo; D. Lemesle; L. Brialix; F. Rodriguez; P.E. Bournet (Building and Environment, 2024)

Ataxia-telangiectasia in Latin America: clinical features, immunodeficiency, and mortality in a multicenter study - Renan A. Pereira; Ellen O. Dantas; Jessica Loekmanwidjaja; Juliana T. L. Mazzucchelli; Carolina S. Aranda; Maria E. G. Serrano; Elisabeth A. De La Cruz Córdoba; Liliana Bezrodnik; Ileana Moreira; Janaira F. S. Ferreira; Vera M. Dantas; Valéria S. F. Sales; et al. (Immunologic Research, 2024)

The history and processes of Titan's equator from the geospatial-topology of spectrally distinct units - N. Kutsop; A.G. Hayes; C. Sotin; J.I. Lunine; S.P.D. Birch; P.M. Corlies; K. Lawrence; S. Le Mouélic; J. Madden; M.J. Malaska; S. Rodriguez; J.M. Soderblom; et al. (Icarus, 2024)

Integrated organismal responses induced by projected levels of CO 2 and temperature exposures in the early life stages of lake sturgeon - Luke D. Belding; Matt J. Thorstensen; Alex R. Quijada‐Rodriguez; William S. Bugg; Gwangseok R. Yoon; Alison R. Loeppky; Garrett J. P. Allen; Alexandra N. Schoen; Madison L. Earhart; Catherine Brandt; Jennifer L. Ali; Dirk Weihrauch; et al. (Molecular Ecology, 2024)
Atmospheric CO 2 and temperature are rising concurrently, and may have profound impacts on the transcriptional, physiological and behavioural responses of aquatic organisms. Further, spring snowmelt may cause transient increases of p CO 2 in many freshwater systems. We examined the behavioural, physiological and transcriptomic responses of an ancient fish, the lake sturgeon ( Acipenser fulvescens ) to projected levels of warming and p CO 2 during its most vulnerable period of life, the first year. Specifically, larval fish were raised in either low (16°C) or high (22°C) temperature, and/or low (1000 μatm) or high (2500 μatm) p CO 2 in a crossed experimental design over approximately 8 months. Following overwintering, lake sturgeon were exposed to a transient increase in p CO 2 of 10,000 μatm, simulating a spring melt based on data in freshwater systems. Transcriptional analyses revealed potential connections to otolith formation and reduced growth in fish exposed to high p CO 2 and temperature in combination. Network analyses of differential gene expression revealed different biological processes among the different treatments on the edges of transcriptional networks. Na + /K + ‐ATPase activity increased in fish not exposed to elevated p CO 2 during development, and mRNA abundance of the β subunit was most strongly predictive of enzyme activity. Behavioural assays revealed a decrease in total activity following an acute CO 2 exposure. These results demonstrate compensatory and compounding mechanisms of p CO 2 and warming dependent on developmental conditions in lake sturgeon. Conserved elements of the cellular stress response across all organisms provide key information for how other freshwater organisms may respond to future climate change.

Increases in regional brain volume across two native South American male populations - Nikhil N. Chaudhari; Phoebe E. Imms; Nahian F. Chowdhury; Margaret Gatz; Benjamin C. Trumble; Wendy J. Mack; E. Meng Law; M. Linda Sutherland; James D. Sutherland; Christopher J. Rowan; L. Samuel Wann; Adel H. Allam; et al. (GeroScience, 2024)
Industrialized environments, despite benefits such as higher levels of formal education and lower rates of infections, can also have pernicious impacts upon brain atrophy. Partly for this reason, comparing age-related brain volume trajectories between industrialized and non-industrialized populations can help to suggest lifestyle correlates of brain health. The Tsimane, indigenous to the Bolivian Amazon, derive their subsistence from foraging and horticulture and are physically active. The Moseten, a mixed-ethnicity farming population, are physically active but less than the Tsimane. Within both populations ( N = 1024; age range = 46–83), we calculated regional brain volumes from computed tomography and compared their cross-sectional trends with age to those of UK Biobank (UKBB) participants ( N = 19,973; same age range). Surprisingly among Tsimane and Moseten (T/M) males, some parietal and occipital structures mediating visuospatial abilities exhibit small but significant increases in regional volume with age. UKBB males exhibit a steeper negative trend of regional volume with age in frontal and temporal structures compared to T/M males. However, T/M females exhibit significantly steeper rates of brain volume decrease with age compared to UKBB females, particularly for some cerebro-cortical structures (e.g., left subparietal cortex). Across the three populations, observed trends exhibit no interhemispheric asymmetry. In conclusion, the age-related rate of regional brain volume change may differ by lifestyle and sex. The lack of brain volume reduction with age is not known to exist in other human population, highlighting the putative role of lifestyle in constraining regional brain atrophy and promoting elements of non-industrialized lifestyle like higher physical activity.

Pathological and transcript analysis of protection induced by MTBVAC and BCG against Mycobacterium tuberculosis infection in rhesus macaques - F.J. Salguero; J. Medley; L. Hunter; I. Ruedas-Torres; A. Bird; E. Puentes; E. Rodriguez; S.J. Waddell; C. Martin; S. Sharpe (Journal of Comparative Pathology, 2024)

Considerations for the development of guidance on dose level selection for developmental and reproductive toxicity studies - R.W. Lewis; A.K. Andrus; J. Arroyo; S. Brescia; P.A. Botham; M. Corvaro; G.P. Daston; T. Hofmann; C. Rodriguez; F. Sewell; B. van Ravenzwaay; K. Wiench; et al. (Regulatory Toxicology and Pharmacology, 2024)

Current deformation along the northern Caribbean plate boundary from GNSS measurements in Cuba - E. Calais; O.F. Gonzalez; E.D. Arango-Arias; B. Moreno; R. Palau; M. Cutie; E. Diez; C. Montenegro; E. Rodriguez Roche; J. Garcia; E. Castellanos; S. Symithe (Tectonophysics, 2023)

Financial and Operational Feasibility Pilot of a Medically Tailored Meal Program - W. Phillips; S. Geneva; M. Yepes-Rios; M. Alejandro-Rodriguez; J. Evans; R. Miles (Journal of the Academy of Nutrition and Dietetics, 2023)

Correction to: Neuromuscular electrical stimulation in garments optimized for compliance - R. Juthberg; J. Flodin; L. Guo; S. Rodriguez; N. K. Persson; P. W. Ackermann (European Journal of Applied Physiology, 2023)

Neuromuscular electrical stimulation in garments optimized for compliance - R. Juthberg; J. Flodin; L. Guo; S. Rodriguez; N. K. Persson; P. W. Ackermann (European Journal of Applied Physiology, 2023)
Purpose Physical inactivity is associated with muscle atrophy and venous thromboembolism, which may be prevented by neuromuscular electrical stimulation (NMES). This study aimed to investigate the effect on discomfort, current amplitude and energy consumption when varying the frequency and phase duration of low-intensity NMES (LI-NMES) via a sock with knitting-integrated transverse textile electrodes (TTE). Methods On eleven healthy participants (four females), calf-NMES via a TTE sock was applied with increasing intensity (mA) until ankle-plantar flexion at which point outcomes were compared when testing frequencies 1, 3, 10 and 36 Hz and phase durations 75, 150, 200, 300 and 400 µs. Discomfort was assessed with a numerical rating scale (NRS, 0–10) and energy consumption was calculated and expressed in milli-Joule (mJ). Significance set to p ﻿≤ 0.05. Results 1 Hz yielded a median (inter-quartile range) NRS of 2.4 (1.0–3.4), significantly lower than both 3 Hz with NRS 2.8 (1.8–4.2), and 10 Hz with NRS 3.4 (1.4–5.4) (both p ≤ .014). Each increase in tested frequency resulted in significantly higher energy consumption, e.g. 0.6 mJ (0.5–0.8) for 1 Hz vs 14.9 mJ (12.3–21.2) for 36 Hz ( p = .003). Longer phase durations had no significant effect on discomfort despite generally requiring significantly lower current amplitudes. Phase durations 150, 200 and 400 µs required significantly lower energy consumption compared to 75 µs (all p ≤ .037). Conclusion LI-NMES applied via a TTE sock produces a relevant plantar flexion of the ankle with the best comfort and lowest energy consumption using 1 Hz and phase durations 150, 200 or 400 µs.

Seagrass Abundance Predicts Surficial Soil Organic Carbon Stocks Across the Range of Thalassia testudinum in the Western North Atlantic - James W. Fourqurean; Justin E. Campbell; O. Kennedy Rhoades; Calvin J. Munson; Johannes R. Krause; Andrew H. Altieri; James G. Douglass; Kenneth L. Heck; Valerie J. Paul; Anna R. Armitage; Savanna C. Barry; Enrique Bethel; et al. (Estuaries and Coasts, 2023)

Metronidazole photodegradation under solar light with UiO-66-NH2 photocatalyst: Mechanisms, pathway, and toxicity assessment - Y.-L. Wang; A. Gómez-Avilés; S. Zhang; J.J. Rodriguez; J. Bedia; C. Belver (Journal of Environmental Chemical Engineering, 2023)

Observation of large scale precursor correlations between cosmic rays and earthquakes with a periodicity similar to the solar cycle - P. Homola; V. Marchenko; A. Napolitano; R. Damian; R. Guzik; D. Alvarez-Castillo; S. Stuglik; O. Ruimi; O. Skorenok; J. Zamora-Saa; J.M. Vaquero; T. Wibig; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2023)

Harmonized human biomonitoring in European children, teenagers and adults: EU-wide exposure data of 11 chemical substance groups from the HBM4EU Aligned Studies (2014–2021) - Eva Govarts; Liese Gilles; Laura Rodriguez Martin; Tiina Santonen; Petra Apel; Paula Alvito; Elena Anastasi; Helle Raun Andersen; Anna-Maria Andersson; Lenka Andryskova; Jean-Philippe Antignac; Brice Appenzeller; et al. (International Journal of Hygiene and Environmental Health, 2023)

The impacts of social determinants of health and cardiometabolic factors on cognitive and functional aging in Colombian underserved populations - Hernando Santamaria-Garcia; Sebastian Moguilner; Odir Antonio Rodriguez-Villagra; Felipe Botero-Rodriguez; Stefanie Danielle Pina-Escudero; Gary O’Donovan; Cecilia Albala; Diana Matallana; Michael Schulte; Andrea Slachevsky; Jennifer S. Yokoyama; Katherine Possin; et al. (GeroScience, 2023)
Global initiatives call for further understanding of the impact of inequity on aging across underserved populations. Previous research in low- and middle-income countries (LMICs) presents limitations in assessing combined sources of inequity and outcomes (i.e., cognition and functionality). In this study, we assessed how social determinants of health (SDH), cardiometabolic factors (CMFs), and other medical/social factors predict cognition and functionality in an aging Colombian population. We ran a cross-sectional study that combined theory- (structural equation models) and data-driven (machine learning) approaches in a population-based study ( N = 23,694; M = 69.8 years) to assess the best predictors of cognition and functionality. We found that a combination of SDH and CMF accurately predicted cognition and functionality, although SDH was the stronger predictor. Cognition was predicted with the highest accuracy by SDH, followed by demographics, CMF, and other factors. A combination of SDH, age, CMF, and additional physical/psychological factors were the best predictors of functional status. Results highlight the role of inequity in predicting brain health and advancing solutions to reduce the cognitive and functional decline in LMICs.

RecruitNet : A global database of plant recruitment networks - Miguel Verdú; Jose L. Garrido; Julio M. Alcántara; Alicia Montesinos‐Navarro; Salomón Aguilar; Marcelo A. Aizen; Ali A. Al‐Namazi; Mohamed Alifriqui; David Allen; Kristina J. Anderson‐Teixeira; Cristina Armas; Jesús M. Bastida; et al. (Ecology, 2023)
Plant recruitment interactions (i.e., what recruits under what) shape the composition, diversity, and structure of plant communities. Despite the huge body of knowledge on the mechanisms underlying recruitment interactions among species, we still know little about the structure of the recruitment networks emerging in ecological communities. Modeling and analyzing the community‐level structure of plant recruitment interactions as a complex network can provide relevant information on ecological and evolutionary processes acting both at the species and ecosystem levels. We report a data set containing 143 plant recruitment networks in 23 countries across five continents, including temperate and tropical ecosystems. Each network identifies the species under which another species recruits. All networks report the number of recruits (i.e., individuals) per species. The data set includes >850,000 recruiting individuals involved in 118,411 paired interactions among 3318 vascular plant species across the globe. The cover of canopy species and open ground is also provided. Three sampling protocols were used: (1) The Recruitment Network (RN) protocol (106 networks) focuses on interactions among established plants (“canopy species”) and plants in their early stages of recruitment (“recruit species”). A series of plots was delimited within a locality, and all the individuals recruiting and their canopy species were identified; (2) The paired Canopy‐Open (pCO) protocol (26 networks) consists in locating a potential canopy plant and identifying recruiting individuals under the canopy and in a nearby open space of the same area; (3) The Georeferenced plot (GP) protocol (11 networks) consists in using information from georeferenced individual plants in large plots to infer canopy‐recruit interactions. Some networks incorporate data for both herbs and woody species, whereas others focus exclusively on woody species. The location of each study site, geographical coordinates, country, locality, responsible author, sampling dates, sampling method, and life habits of both canopy and recruit species are provided. This database will allow researchers to test ecological, biogeographical, and evolutionary hypotheses related to plant recruitment interactions. There are no copyright restrictions on the data set; please cite this data paper when using these data in publications.

PFAS levels and determinants of variability in exposure in European teenagers – Results from the HBM4EU aligned studies (2014–2021) - D. Richterová; E. Govarts; L. Fábelová; K. Rausová; L. Rodriguez Martin; L. Gilles; S. Remy; A. Colles; L. Rambaud; M. Riou; C. Gabriel; D. Sarigiannis; et al. (International Journal of Hygiene and Environmental Health, 2023)

Coral‐bleaching responses to climate change across biological scales - Robert van Woesik; Tom Shlesinger; Andréa G. Grottoli; Rob J. Toonen; Rebecca Vega Thurber; Mark E. Warner; Ann Marie Hulver; Leila Chapron; Rowan H. McLachlan; Rebecca Albright; Eric Crandall; Thomas M. DeCarlo; et al. (Global Change Biology, 2022)
The global impacts of climate change are evident in every marine ecosystem. On coral reefs, mass coral bleaching and mortality have emerged as ubiquitous responses to ocean warming, yet one of the greatest challenges of this epiphenomenon is linking information across scientific disciplines and spatial and temporal scales. Here we review some of the seminal and recent coral‐bleaching discoveries from an ecological, physiological, and molecular perspective. We also evaluate which data and processes can improve predictive models and provide a conceptual framework that integrates measurements across biological scales. Taking an integrative approach across biological and spatial scales, using for example hierarchical models to estimate major coral‐reef processes, will not only rapidly advance coral‐reef science but will also provide necessary information to guide decision‐making and conservation efforts. To conserve reefs, we encourage implementing mesoscale sanctuaries (thousands of km 2 ) that transcend national boundaries. Such networks of protected reefs will provide reef connectivity, through larval dispersal that transverse thermal environments, and genotypic repositories that may become essential units of selection for environmentally diverse locations. Together, multinational networks may be the best chance corals have to persist through climate change, while humanity struggles to reduce emissions of greenhouse gases to net zero.

Novel Fusarium wilt resistance genes uncovered in natural and cultivated strawberry populations are found on three non-homoeologous chromosomes - Dominique D. A. Pincot; Mitchell J. Feldmann; Michael A. Hardigan; Mishi V. Vachev; Peter M. Henry; Thomas R. Gordon; Marta Bjornson; Alan Rodriguez; Nicolas Cobo; Randi A. Famula; Glenn S. Cole; Gitta L. Coaker; et al. (Theoretical and Applied Genetics, 2022)
Key Message Several Fusarium wilt resistance genes were discovered, genetically and physically mapped, and rapidly deployed via marker-assisted selection to develop cultivars resistant to Fusarium oxysporum f. sp. fragariae , a devastating soil-borne pathogen of strawberry . Abstract Fusarium wilt, a soilborne disease caused by Fusarium oxysporum f. sp. fragariae , poses a significant threat to strawberry ( Fragaria $$×$$ × ananassa ) production in many parts of the world. This pathogen causes wilting, collapse, and death in susceptible genotypes. We previously identified a dominant gene ( FW1 ) on chromosome 2B that confers resistance to race 1 of the pathogen, and hypothesized that gene-for-gene resistance to Fusarium wilt was widespread in strawberry. To explore this, a genetically diverse collection of heirloom and modern cultivars and octoploid ecotypes were screened for resistance to Fusarium wilt races 1 and 2. Here, we show that resistance to both races is widespread in natural and domesticated populations and that resistance to race 1 is conferred by partially to completely dominant alleles among loci ( FW1 , FW2 , FW3 , FW4 , and FW5 ) found on three non-homoeologous chromosomes (1A, 2B, and 6B). The underlying genes have not yet been cloned and functionally characterized; however, plausible candidates were identified that encode pattern recognition receptors or other proteins known to confer gene-for-gene resistance in plants. High-throughput genotyping assays for SNPs in linkage disequilibrium with FW1 - FW5 were developed to facilitate marker-assisted selection and accelerate the development of race 1 resistant cultivars. This study laid the foundation for identifying the genes encoded by FW1-FW5 , in addition to exploring the genetics of resistance to race 2 and other races of the pathogen, as a precaution to averting a Fusarium wilt pandemic.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

“Right diet for the right person”: a focus group study of nutritionist-dietitians’ perspectives on nutritional genomics and gene-based nutrition advice - Jacus S. Nacis; Marilou R. Galang; Jason Paolo H. Labrador; Milflor S. Gonzales; Aurora Maria Francesca D. Dablo; Diana Glades A. Domalanta-Ronquillo; Victor Franco J. Alfonso; Idelia G. Glorioso; Marietta P. Rodriguez (Journal of Community Genetics, 2022)
Advances in nutritional genomics are intended to revolutionize nutrition practice. A basic understanding of nutritional genomics among nutritionist-dietitians is critical for such advancements to occur. As a precedent to the development and integration of gene-based nutrition advice, this study aimed to assess hospital-based nutritionist-dietitians’ perceptions of nutritional genomics. A total of ten focus group discussions (FGDs) with sixty-one registered nutritionist-dietitians (RNDs) from hospitals in the National Capital Region (NCR), Philippines, were conducted from October to November 2019. Data were collected using a pretested semistructured discussion guide, and thematic analysis was subsequently performed. Diverging perceptions about nutritional genomics were noted among the FGD participants. Five themes emerged relating to the enablers and barriers of gene-based nutrition advice: training and capacity building, the extent of information to be disclosed, cost, ethical considerations, and government support. Themes related to the desired features of the gene-based nutrition advice included being consent-driven, cost-effective, technology-oriented, and guided by standards. The results of this study suggest that training and continued learning will equip RNDs to provide nutrition advice based on genetic information. However, other factors, such as cost and ethical considerations, are critical dimensions that need to be acknowledged and addressed before integrating gene-based advice into nutrition practice.

A Comprehensive, FAIR File Format for Neuroanatomical Structure Modeling - A. E. Sullivan; S. J. Tappan; P. J. Angstman; A. Rodriguez; G. C. Thomas; D. M. Hoppes; M. A. Abdul-Karim; M. L. Heal; Jack R. Glaser (Neuroinformatics, 2022)
With advances in microscopy and computer science, the technique of digitally reconstructing, modeling, and quantifying microscopic anatomies has become central to many fields of biological research. MBF Bioscience has chosen to openly document their digital reconstruction file format, the Neuromorphological File Specification, available at www.mbfbioscience.com/filespecification (Angstman et al., 2020). The format, created and maintained by MBF Bioscience, is broadly utilized by the neuroscience community. The data format’s structure and capabilities have evolved since its inception, with modifications made to keep pace with advancements in microscopy and the scientific questions raised by worldwide experts in the field. More recent modifications to the neuromorphological file format ensure it abides by the Findable, Accessible, Interoperable, and Reusable (FAIR) data principles promoted by the International Neuroinformatics Coordinating Facility (INCF; Wilkinson et al., Scientific Data, 3 , 160018,, 2016). The incorporated metadata make it easy to identify and repurpose these data types for downstream applications and investigation. This publication describes key elements of the file format and details their relevant structural advantages in an effort to encourage the reuse of these rich data files for alternative analysis or reproduction of derived conclusions.

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation - R. J. Longchamps; S. Y. Yang; C. A. Castellani; W. Shi; J. Lane; M. L. Grove; T. M. Bartz; C. Sarnowski; C. Liu; K. Burrows; A. L. Guyatt; T. R. Gaunt; et al. (Human Genetics, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes ( p = 3.09 × 10 –15 ) and the gene ontology (GO) terms for mtDNA metabolism ( p = 1.43 × 10 –8 ) and mtDNA replication ( p = 1.2 × 10 –7 ). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall ( p = 0.044) and non-cancer mortality ( p = 6.56 × 10 –4 ).

Recognizing Indigenous peoples’ and local communities’ rights and agency in the post-2020 Biodiversity Agenda - Victoria Reyes-García; Álvaro Fernández-Llamazares; Yildiz Aumeeruddy-Thomas; Petra Benyei; Rainer W. Bussmann; Sara K. Diamond; David García-del-Amo; Sara Guadilla-Sáez; Natalia Hanazaki; Nicolas Kosoy; Margarita Lavides; Ana C. Luz; et al. (Ambio, 2022)
The Convention on Biological Diversity is defining the goals that will frame future global biodiversity policy in a context of rapid biodiversity decline and under pressure to make transformative change. Drawing on the work of Indigenous and non-Indigenous scholars, we argue that transformative change requires the foregrounding of Indigenous peoples’ and local communities’ rights and agency in biodiversity policy. We support this argument with four key points. First, Indigenous peoples and local communities hold knowledge essential for setting realistic and effective biodiversity targets that simultaneously improve local livelihoods. Second, Indigenous peoples’ conceptualizations of nature sustain and manifest CBD’s 2050 vision of “Living in harmony with nature.” Third, Indigenous peoples’ and local communities’ participation in biodiversity policy contributes to the recognition of human and Indigenous peoples’ rights. And fourth, engagement in biodiversity policy is essential for Indigenous peoples and local communities to be able to exercise their recognized rights to territories and resources.

NGS and phenotypic ontology-based approaches increase the diagnostic yield in syndromic retinal diseases - I. Perea-Romero; F. Blanco-Kelly; I. Sanchez-Navarro; I. Lorda-Sanchez; S. Tahsin-Swafiri; A. Avila-Fernandez; I. Martin-Merida; M. J. Trujillo-Tiebas; R. Lopez-Rodriguez; M. Rodriguez de Alba; I. F. Iancu; R. Romero; et al. (Human Genetics, 2021)
Syndromic retinal diseases (SRDs) are a group of complex inherited systemic disorders, with challenging molecular underpinnings and clinical management. Our main goal is to improve clinical and molecular SRDs diagnosis, by applying a structured phenotypic ontology and next-generation sequencing (NGS)-based pipelines. A prospective and retrospective cohort study was performed on 100 probands with an a priori diagnosis of non-Usher SRDs, using available clinical data, including Human Phenotype Ontology annotation, and further classification into seven clinical categories (ciliopathies, specific syndromes and five others). Retrospective molecular diagnosis was assessed using different molecular and bioinformatic methods depending on availability. Subsequently, uncharacterized probands were prospectively screened using other NGS approaches to extend the number of analyzed genes. After phenotypic classification, ciliopathies were the most common SRD (35%). A global characterization rate of 52% was obtained, with six cases incompletely characterized for a gene that partially explained the phenotype. An improved characterization rate was achieved addressing prospective cases (83%) and well-recognizable syndrome (62%) subgroups. The 27% of the fully characterized cases were reclassified into a different clinical category after identification of the disease-causing gene. Clinical-exome sequencing is the most appropriate first-tier approach for prospective cases, whereas whole-exome sequencing and bioinformatic reanalysis increases the diagnosis of uncharacterized retrospective cases to 45%, mostly those with unspecific symptoms. Our study describes a comprehensive approach to SRDs in daily clinical practice and the importance of thorough clinical assessment and selection of the most appropriate molecular test to be used to solve these complex cases and elucidate novel associations.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Trade‐offs between reducing complex terminology and producing accurate interpretations from environmental DNA: Comment on “Environmental DNA: What's behind the term?” by Pawlowski et al., (2020) - Naiara Rodriguez‐Ezpeleta; Olivier Morissette; Colin W. Bean; Shivakumara Manu; Pritam Banerjee; Anaïs Lacoursière‐Roussel; Kingsly C. Beng; S. Elizabeth Alter; Fabian Roger; Luke E. Holman; Kathryn A. Stewart; Michael T. Monaghan; et al. (Molecular Ecology, 2021)
In a recent paper, “Environmental DNA: What's behind the term? Clarifying the terminology and recommendations for its future use in biomonitoring,” Pawlowski et al . argue that the term eDNA should be used to refer to the pool of DNA isolated from environmental samples, as opposed to only extra‐organismal DNA from macro‐organisms. We agree with this view. However, we are concerned that their proposed two‐level terminology specifying sampling environment and targeted taxa is overly simplistic and might hinder rather than improve clear communication about environmental DNA and its use in biomonitoring. This terminology is based on categories that are often difficult to assign and uninformative, and it overlooks a fundamental distinction within eDNA: the type of DNA (organismal or extra‐organismal) from which ecological interpretations are derived.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Nutritional and ecotoxicological aspects of the acidotolerant alga Keratococcus rhaphidioides (Chlorophyta): a potential candidate for algal mediated bioremediation of extremely acidic waters - J. M. Cabrera; S. S. Schultz; G. D. Baffico; M. C. Rodriguez; F. L. Pedrozo; M. M. Diaz (Journal of Applied Phycology, 2021)

New insights into the mechanisms underlying 5-fluorouracil-induced intestinal toxicity based on transcriptomic and metabolomic responses in human intestinal organoids - Daniela Rodrigues; Terezinha de Souza; Luke Coyle; Matteo Di Piazza; Bram Herpers; Sofia Ferreira; Mian Zhang; Johanna Vappiani; Daniel C. Sévin; Attila Gabor; Anthony Lynch; Seung-Wook Chung; et al. (Archives of Toxicology, 2021)
5-Fluorouracil (5-FU) is a widely used chemotherapeutical that induces acute toxicity in the small and large intestine of patients. Symptoms can be severe and lead to the interruption of cancer treatments. However, there is limited understanding of the molecular mechanisms underlying 5-FU-induced intestinal toxicity. In this study, well-established 3D organoid models of human colon and small intestine (SI) were used to characterize 5-FU transcriptomic and metabolomic responses. Clinically relevant 5-FU concentrations for in vitro testing in organoids were established using physiologically based pharmacokinetic simulation of dosing regimens recommended for cancer patients, resulting in exposures to 10, 100 and 1000 µM. After treatment, different measurements were performed: cell viability and apoptosis; image analysis of cell morphological changes; RNA sequencing; and metabolome analysis of supernatant from organoids cultures. Based on analysis of the differentially expressed genes, the most prominent molecular pathways affected by 5-FU included cell cycle, p53 signalling, mitochondrial ATP synthesis and apoptosis. Short time-series expression miner demonstrated tissue-specific mechanisms affected by 5-FU, namely biosynthesis and transport of small molecules, and mRNA translation for colon; cell signalling mediated by Rho GTPases and fork-head box transcription factors for SI. Metabolomic analysis showed that in addition to the effects on TCA cycle and oxidative stress in both organoids, tissue-specific metabolic alterations were also induced by 5-FU. Multi-omics integration identified transcription factor E2F1, a regulator of cell cycle and apoptosis, as the best key node across all samples. These results provide new insights into 5-FU toxicity mechanisms and underline the relevance of human organoid models in the safety assessment in drug development.

Roundup negatively impacts the behavior and nerve function of the Madagascar hissing cockroach (Gromphadorhina portentosa) - Megha Kanabar; Samuel Bauer; Zimuzo M. Ezedum; Ian P. Dwyer; William S. Moore; Gabriella Rodriguez; Aditya Mall; Anne T. Littleton; Michael Yudell; Jenil Kanabar; Wade J. Tucker; Emily R. Daniels; et al. (Environmental Science and Pollution Research, 2021)

Comparison of real and simulated lava flows in the Holocene volcanism of Gran Canaria (Canary Islands, Spain) with Q-LavHA: contribution to volcanic hazard management - A. Rodriguez-Gonzalez; M. Aulinas; S. Mossoux; F. J. Perez-Torrado; J. L. Fernandez-Turiel; M. Cabrera; C. Prieto-Torrell (Natural Hazards, 2021)

Correction to: Impact of acute high‑intensity interval exercise on plasma pentraxin 3 and endothelial function in obese individuals—a pilot study - Aaron L. Slusher; Brandon G. Fico; Katelyn M. Dodge; Ryan S. Garten; Peter J. Ferrandi; Alexandra A. Rodriguez; Gabriel Pena; Chun-Jung Huang (European Journal of Applied Physiology, 2021)

Impact of acute high-intensity interval exercise on plasma pentraxin 3 and endothelial function in obese individuals—a pilot study - Aaron L. Slusher; Brandon G. Fico; Katelyn M. Dodge; Ryan S. Garten; Peter J. Ferrandi; Alexandra A. Rodriguez; Gabriel Pena; Chun-Jung Huang (European Journal of Applied Physiology, 2021)

Managing groundwater supplies subject to drought: perspectives on current status and future priorities from England (UK) - M. J. Ascott; J. P. Bloomfield; I. Karapanos; C. R. Jackson; R. S. Ward; A. B. McBride; B. Dobson; N. Kieboom; I. P. Holman; A. F. Van Loon; E. J. Crane; B. Brauns; et al. (Hydrogeology Journal, 2021)
Effective management of groundwater resources during drought is essential. How is groundwater currently managed during droughts, and in the face of environmental change, what should be the future priorities? Four themes are explored, from the perspective of groundwater management in England (UK): (1) integration of drought definitions; (2) enhanced fundamental monitoring; (3) integrated modelling of groundwater in the water cycle; and (4) better information sharing. Whilst these themes are considered in the context of England, globally, they are relevant wherever groundwater is affected by drought.

Superoxide-mediated oxidative stress accelerates skeletal muscle atrophy by synchronous activation of proteolytic systems - Young C. Jang; Karl Rodriguez; Michael S. Lustgarten; Florian L. Muller; Arunabh Bhattacharya; Anson Pierce; Jeongmoon J. Choi; Nan Hee Lee; Asish Chaudhuri; Arlan G. Richardson; Holly Van Remmen (GeroScience, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Dynamics of volatilomes emitted during cross-talking of plant-growth-promoting bacteria and the phytopathogen, Fusarium solani - A. Gutiérrez-Santa Ana; H. A. Carrillo-Cerda; J. Rodriguez-Campos; J. B. Velázquez-Fernández; O. A. Patrón-Soberano; S. M. Contreras-Ramos (World Journal of Microbiology and Biotechnology, 2020)

Amphetamine-induced striatal dopamine release in schizotypal personality disorder - Judy L. Thompson; Daniel R. Rosell; Mark Slifstein; Xiaoyan Xu; Ethan G. Rothstein; Yosefa A. Modiano; Lawrence S. Kegeles; Harold W. Koenigsberg; Antonia S. New; Erin A. Hazlett; Margaret M. McClure; M. Mercedes Perez-Rodriguez; et al. (Psychopharmacology, 2020)

Mislocalization of SMN from the I-band and M-band in human skeletal myofibers in spinal muscular atrophy associates with primary structural alterations of the sarcomere - María T. Berciano; María S. Castillo-Iglesias; J. Fernando Val-Bernal; Vanesa Lafarga; José C. Rodriguez-Rey; Miguel Lafarga; Olga Tapia (Cell and Tissue Research, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Microbiome of the deep Lake Baikal, a unique oxic bathypelagic habitat - Pedro J. Cabello‐Yeves; Tamara I. Zemskaya; Alexandra S. Zakharenko; Mariya V. Sakirko; Vyacheslav G. Ivanov; Rohit Ghai; Francisco Rodriguez‐Valera (Limnology and Oceanography, 2020)
Lake Baikal is the deepest lake in the world. Its depth provides the only bathypelagic (> 1000 m deep) freshwater habitat on Earth and its oxic, ultra‐oligotrophic features make it a freshwater counterpart of the deep ocean. Here we have analyzed metagenomes from 1250 and 1350 m deep samples and built 231 metagenome‐assembled genomes (MAGs). We detected high fractions of Thaumarchaeota (ca. 20% of 16S rRNA reads) and members of the candidate phyla radiation (CPR) (3–4.5%). Among the MAGs, we obtained ammonia‐oxidizing archaea (AOA, Nitrosopumilaceae) and bacteria (AOB, Nitrosomonadaceae), and nitrite‐oxidizers (Nitrospirae) indicating very active nitrification. A new clade of freshwater SAR202 Chloroflexi and methanotrophs ( Methyloglobulus ) were also remarkably abundant, the latter reflecting a possible role of methane oxidation as well. Novel species of streamlined and cosmopolitan bacteria such as Ca. Fonsibacter or acI Actinobacteria were more abundant at the surface but also present in deep waters. Conversely, CPRs, Myxococcales, Chloroflexi, DPANN (Diapherotrites, Parvarchaeota, Aenigmarchaeota, Nanoarchaeota and Nanohaloarchaeota) archaea, or Gammaproteobacteria were found only in bathypelagic samples. We noted various important taxonomic and metabolic differences between deep aphotic region of Lake Baikal and marine waters of similar depth: Betaproteobacteriales, CPR, and DPANN superphylum were only found in bathypelagic Baikal, while Deltaproteobacteria, Gammaproteobacteria, or Alphaproteobacteria prevailed in oceanic samples. The genes mediating ammonia and methane oxidation, aromatic compound degradation, or alkane/methanesulfonate monooxygenases were detected in higher numbers in deep Baikal compared to their oceanic counterparts or its own surface. Overall, depth seems to be less relevant than salinity in configuring the microbial community.

Three-dimensional regional bi-ventricular shape remodeling is associated with exercise capacity in endurance athletes - G. Bernardino; M. Sanz de la Garza; B. Domenech-Ximenos; S. Prat-Gonzàlez; R. J. Perea; I. Blanco; F. Burgos; A. Sepulveda-Martinez; M. Rodriguez-Lopez; F. Crispi; C. Butakoff; M. A. González Ballester; et al. (European Journal of Applied Physiology, 2020)

A Metabolic Intravascular Platform to Study FDG Uptake in Vascular Injury - F. Franchi; M. Olthoff; J. Krier; C. Noble; M. Al-Hijji; V. Ramaswamy; T. Witt; M. Burke; M. Benscoter; A. Lerman; G. S. Sandhu; M. Rodriguez-Porcel (Cardiovascular Engineering and Technology, 2020)

Sub-Arctic Field Degradation of Metsulfuron-Methyl in Two Alaskan Soils and Microbial Community Composition Effects - Patrick L. Tomco; Steven S. Seefeldt; Katinna Rodriguez-Baisi; Jasmine J. Hatton; Khrystyne N. Duddleston (Water, Air, & Soil Pollution, 2020)

Sexual recombination within the “Kranich” race of the yellow rust fungus Puccinia striiformis f.sp. tritici on Berberis vulgaris - J. Rodriguez-Algaba; M. S. Hovmøller; A. F. Justesen (European Journal of Plant Pathology, 2020)

Evaluating the performance of freshwater macroalgae in the bioremediation of nutrient-enriched water in temperate environments - J. M. Valero-Rodriguez; S. E. Swearer; T. Dempster; R. de Nys; A. J. Cole (Journal of Applied Phycology, 2020)

SPEXOR passive spinal exoskeleton decreases metabolic cost during symmetric repetitive lifting - S. J. Baltrusch; J. H. van Dieën; A. S. Koopman; M. B. Näf; C. Rodriguez-Guerrero; J. Babič; H. Houdijk (European Journal of Applied Physiology, 2020)

Australia-Asian monsoon in two versions of the UK Met Office Unified Model and their impacts on tropical–extratropical teleconnections - L. Jin; H. Zhang; A. Moise; G. Martin; S. Milton; J. Rodriguez (Climate Dynamics, 2019)

Defining the indigenous ranges of species to account for geographic and taxonomic variation in the history of human impacts: reply to Sanderson 2019 - P. J. Stephenson; Molly K. Grace; H. Resit Akçakaya; Ana S. L. Rodrigues; Barney Long; David P. Mallon; Erik Meijaard; Jon Paul Rodriguez; Richard P. Young; Thomas M. Brooks; Craig Hilton‐Taylor (Conservation Biology, 2019)

Reorganization of the nuclear compartments involved in transcription and RNA processing in myonuclei of type I spinal muscular atrophy - María S. Castillo-Iglesias; María T. Berciano; J. Oriol Narcis; J. Fernando Val-Bernal; José C. Rodriguez-Rey; Olga Tapia; Miguel Lafarga (Histochemistry and Cell Biology, 2019)

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

Bioethanol Production From Sugarcane Bagasse Hemicellulose Hydrolysate by Immobilized S. shehatae in a Fluidized Bed Fermenter Under Magnetic Field - Kelly J. Dussán; Oselys Rodriguez Justo; Victor Haber Perez; Geraldo F. David; Euripedes Garcia Silveira Junior; Silvio S. da Silva (BioEnergy Research, 2019)

Nutritional evaluation and productivity of supplemented sheep grazing in semiarid rangeland of northeastern Brazil - A. R. Araújo; N. M. Rodriguez; Marcos Cláudio Pinheiro Rogério; I. Borges; E. O. S. Saliba; S. A. Santos; R. C. F. F. Pompeu; F. E. P. Fernandes; J. P. Monteiro; J. P. Muir (Tropical Animal Health and Production, 2019)

Doubting dung: eDNA reveals high rates of misidentification in diverse European ungulate communities - Robert Spitzer; Marcin Churski; Annika Felton; Marco Heurich; Dries P. J. Kuijper; Marietjie Landman; Esther Rodriguez; Navinder J. Singh; Pierre Taberlet; Suzanne T. S. van Beeck Calkoen; Fredrik Widemo; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2019)

Serum P-glycoprotein level: a potential biomarker of DMARD failure in patients with rheumatoid arthritis - E. E. Perez-Guerrero; L. Gonzalez-Lopez; J. F. Muñoz-Valle; J. C. Vasquez-Jimenez; M. Ramirez-Villafaña; E. N. Sanchez-Rodriguez; S. R. Gutierrez-Ureña; S. Cerpa-Cruz; E. A. Aguilar-Chavez; E. G. Cardona-Muñoz; M. L. Vazquez-Villegas; A. M. Saldaña-Cruz; et al. (Inflammopharmacology, 2018)

BRAZIL ROAD‐KILL: a data set of wildlife terrestrial vertebrate road‐kills - Clara Grilo; Michely R. Coimbra; Rafaela C. Cerqueira; Priscilla Barbosa; Rubem A. P. Dornas; Larissa O. Gonçalves; Fernanda Z. Teixeira; Igor Pfeifer Coelho; Brenda R. Schmidt; Diana L. K. Pacheco; Gabriela Schuck; Isadora B. Esperando; et al. (Ecology, 2018)
Mortality from collision with vehicles is the most visible impact of road traffic on wildlife. Mortality due to roads (hereafter road‐kill) can affect the dynamic of populations of many species and can, therefore, increase the risk of local decline or extinction. This is especially true in Brazil, where plans for road network upgrading and expansion overlaps biodiversity hotspot areas, which are of high importance for global conservation. Researchers, conservationists and road planners face the challenge to define a national strategy for road mitigation and wildlife conservation. The main goal of this dataset is a compilation of geo‐referenced road‐kill data from published and unpublished road surveys. This is the first Data Paper in the BRAZIL series (see ATLANTIC , NEOTROPICAL , and BRAZIL collections of Data Papers published in Ecology ), which aims make public road‐kill data for species in the Brazilian Regions. The dataset encompasses road‐kill records from 45 personal communications and 26 studies published in peer‐reviewed journals, theses and reports. The road‐kill dataset comprises 21,512 records, 83% of which are identified to the species level (n = 450 species). The dataset includes records of 31 amphibian species, 90 reptile species, 229 bird species, and 99 mammal species. One species is classified as Endangered, eight as Vulnerable and twelve as Near Threatened. The species with the highest number of records are: Didelphis albiventris (n = 1,549), Volatinia jacarina (n = 1,238), Cerdocyon thous (n = 1,135), Helicops infrataeniatus (n = 802), and Rhinella icterica (n = 692). Most of the records came from southern Brazil. However, observations of the road‐kill incidence for non‐Least Concern species are more spread across the country. This dataset can be used to identify which taxa seems to be vulnerable to traffic, analyze temporal and spatial patterns of road‐kill at local, regional and national scales and also used to understand the effects of road‐kill on population persistence. It may also contribute to studies that aims to understand the influence of landscape and environmental influences on road‐kills, improve our knowledge on road‐related strategies on biodiversity conservation and be used as complementary information on large‐scale and macroecological studies. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Invasive pulmonary aspergillosis is associated with adverse clinical outcomes in critically ill patients receiving veno-venous extracorporeal membrane oxygenation - I. Rodriguez-Goncer; S. Thomas; P. Foden; M. D. Richardson; A. Ashworth; J. Barker; C. G. Geraghty; E. G. Muldoon; T. W. Felton (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Adapting clonally propagated crops to climatic changes: a global approach for taro (Colocasia esculenta (L.) Schott) - V. Lebot; V. Tuia; A. Ivancic; G. V. H. Jackson; F. Saborio; G. Reyes; S. Rodriguez; G. Robin; R. Traoré; L. Aboagye; J. Onyeka; W. van Rensburg; et al. (Genetic Resources and Crop Evolution, 2018)

Brain-specific HIV Nef identified in multiple patients with neurological disease - Susanna L. Lamers; Gary B. Fogel; Enoch S. Liu; Andrew E. Barbier; Christopher W. Rodriguez; Elyse J. Singer; David J. Nolan; Rebecca Rose; Michael S. McGrath (Journal of NeuroVirology, 2018)

Anisotropic larval connectivity and metapopulation structure driven by directional oceanic currents in a marine fish targeted by small-scale fisheries - Adrian Munguia-Vega; S. Guido Marinone; David A. Paz-Garcia; Alfredo Giron-Nava; Tomas Plomozo-Lugo; Ollin Gonzalez-Cuellar; Amy Hudson Weaver; Francisco J. García-Rodriguez; Hector Reyes-Bonilla (Marine Biology, 2018)

Photosynthetic performance and pigment composition of Macrocystis pyrifera (Laminariales, Phaeophyceae) along a gradient of depth and seasonality in the ecoregion of Magellan, Chile - J. Marambio; J. P. Rodriguez; F. Mendez; P. Ocaranza; S. Rosenfeld; J. Ojeda; R. Rautenberger; K. Bischof; J. Terrados; A. Mansilla (Journal of Applied Phycology, 2017)

Nutritional properties of dishes prepared with sub-Antarctic macroalgae—an opportunity for healthy eating - Ma. S. Astorga-España; A. Mansilla; J. Ojeda; J. Marambio; S. Rosenfeld; F. Mendez; J. P. Rodriguez; P. Ocaranza (Journal of Applied Phycology, 2017)

Effects of diurnal temperature range and drought on wheat yield in Spain - S. Hernandez-Barrera; C. Rodriguez-Puebla; A. J. Challinor (Theoretical and Applied Climatology, 2017)

Adaptation of Shigella flexneri to starvation: morphology, outer membrane proteins and lipopolysaccharide changes - K. Chourabi; F. Torrella; S. Kloula; J. A. Rodriguez; I. Trabelsi; S. Campoy; A. Landoulsi; A. Chatti (Arabian Journal of Geosciences, 2017)

A comparison of psychotic symptoms in subjects with methamphetamine versus cocaine dependence - Peter D Alexander; Kristina M Gicas; Taylor S Willi; Clara N Kim; Veronika Boyeva; Ric M Procyshyn; Geoff N. Smith; Allen E Thornton; William J Panenka; Andrea A. Jones; Fidel Vila-Rodriguez; Donna J. Lang; et al. (Psychopharmacology, 2017)

Seasonal variations of the photosynthetic activity and pigment concentrations in different reproductive phases of Gigartina skottsbergii (Rhodophyta, Gigartinales) in the Magellan region, sub-Antarctic Chile - J. Marambio; F. Mendez; P. Ocaranza; J. P. Rodriguez; S. Rosenfeld; J. Ojeda; S. Murcia; J. Terrados; K. Bischof; A . Mansilla (Journal of Applied Phycology, 2017)

Spatio-temporal monitoring by ground-based and air- and space-borne lidars of a moderate Saharan dust event affecting southern Europe in June 2013 in the framework of the ADRIMED/ChArMEx campaign - R. Barragan; M. Sicard; J. Totems; J. F. Léon; F. Dulac; M. Mallet; J. Pelon; L. Alados-Arboledas; A. Amodeo; P. Augustin; A. Boselli; J. A. Bravo-Aranda; et al. (Air Quality, Atmosphere & Health, 2017)

Lizards fail to plastically adjust nesting behavior or thermal tolerance as needed to buffer populations from climate warming - Rory S. Telemeco; Brooke Fletcher; Ofir Levy; Angela Riley; Yesenia Rodriguez‐Sanchez; Colton Smith; Collin Teague; Amanda Waters; Michael J. Angilletta; Lauren B. Buckley (Global Change Biology, 2017)
Although observations suggest the potential for phenotypic plasticity to allow adaptive responses to climate change, few experiments have assessed that potential. Modeling suggests that Sceloporus tristichus lizards will need increased nest depth, shade cover, or embryonic thermal tolerance to avoid reproductive failure resulting from climate change. To test for such plasticity, we experimentally examined how maternal temperatures affect nesting behavior and embryonic thermal sensitivity. The temperature regime that females experienced while gravid did not affect nesting behavior, but warmer temperatures at the time of nesting reduced nest depth. Additionally, embryos from heat‐stressed mothers displayed increased sensitivity to high‐temperature exposure. Simulations suggest that critically low temperatures, rather than high temperatures, historically limit development of our study population. Thus, the plasticity needed to buffer this population has not been under selection. Plasticity will likely fail to compensate for ongoing climate change when such change results in novel stressors.

Free-living culturable bacteria and protozoa from the rhizoplanes of three floating aquatic plant species - E. Quisehuatl-Tepexicuapan; R. Ferrera-Cerrato; H. V. Silva-Rojas; S. Rodriguez-Zaragoza; A. Alarcón; J. J. Almaraz-Suárez (Plant Biosystems, 2016)

Genotype Number and Allelic Diversity Overview in the National Collection of Chilean Potatoes - M. Muñoz; C. Folch; F. Rodriguez; J. Kalazich; S. Orena; J. Santos; R. Vargas; A. Fahrenkrog; A. Puga (Potato Research, 2016)

Neisseria gonorrhoeae antimicrobial susceptibility in Barcelona: penA, ponA, mtrR, and porB mutations and NG-MAST sequence types associated with decreased susceptibility to cephalosporins - J. Serra-Pladevall; M. J. Barberá; S. Rodriguez; R. Bartolomé-Comas; G. Roig; R. Juvé; A. Andreu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Amphibian‐killing chytrid in B razil comprises both locally endemic and globally expanding populations - T. S. Jenkinson; C. M. Betancourt Román; C. Lambertini; A. Valencia‐Aguilar; D. Rodriguez; C. H. L. Nunes‐de‐Almeida; J. Ruggeri; A. M. Belasen; D. da Silva Leite; K. R. Zamudio; J. E. Longcore; L. F. Toledo; et al. (Molecular Ecology, 2016)
Chytridiomycosis, caused by the fungus Batrachochytrium dendrobatidis ( Bd ), is the emerging infectious disease implicated in recent population declines and extinctions of amphibian species worldwide. Bd strains from regions of disease‐associated amphibian decline to date have all belonged to a single, hypervirulent clonal genotype ( Bd ‐ GPL ). However, earlier studies in the Atlantic Forest of southeastern Brazil detected a novel, putatively enzootic lineage ( Bd ‐Brazil), and indicated hybridization between Bd ‐ GPL and Bd ‐Brazil. Here, we characterize the spatial distribution and population history of these sympatric lineages in the Brazilian Atlantic Forest. To investigate the genetic structure of Bd in this region, we collected and genotyped Bd strains along a 2400‐km transect of the Atlantic Forest. Bd ‐Brazil genotypes were restricted to a narrow geographic range in the southern Atlantic Forest, while Bd ‐ GPL strains were widespread and largely geographically unstructured. Bd population genetics in this region support the hypothesis that the recently discovered Brazilian lineage is enzootic in the Atlantic Forest of Brazil and that Bd ‐ GPL is a more recently expanded invasive. We collected additional hybrid isolates that demonstrate the recurrence of hybridization between panzootic and enzootic lineages, thereby confirming the existence of a hybrid zone in the Serra da Graciosa mountain range of Paraná State. Our field observations suggest that Bd ‐ GPL may be more infective towards native Brazilian amphibians, and potentially more effective at dispersing across a fragmented landscape. We also provide further evidence of pathogen translocations mediated by the Brazilian ranaculture industry with implications for regulations and policies on global amphibian trade.

Assessing stakeholder impacts and adaptation to low water-levels: the Trent-Severn waterway - J. M. A. Coleman; F. S. Sosa-Rodriguez; L. D. Mortsch; P. J. Deadman (Climatic Change, 2016)

Differential gene transcription, biochemical responses, and cytotoxicity assessment in Pacific oyster Crassostrea gigas exposed to ibuprofen - Miguel A. S. Serrano; Maria Gonzalez-Rey; Jacó J. Mattos; Fabrício Flores-Nunes; Álvaro C. P. Mello; Flávia L. Zacchi; Clei E. Piazza; Marília N. Siebert; Rômi S. Piazza; Diana Alvarez-Muñoz; Sara Rodriguez-Mozaz; Damià Barceló; et al. (Environmental Science and Pollution Research, 2015)

Cellular metabolism of unnatural sialic acid precursors - Nam D. Pham; Charles S. Fermaintt; Andrea C. Rodriguez; Janet E. McCombs; Nicole Nischan; Jennifer J. Kohler (Glycoconjugate Journal, 2015)

Identifying the pollen of an extinct spruce species in the Late Quaternary sediments of the Tunica Hills region, south‐eastern United States - L. MANDER; J. RODRIGUEZ; P. G. MUELLER; S. T. JACKSON; S. W. PUNYASENA (Journal of Quaternary Science, 2014)
Late Quaternary fluvial deposits in the Tunica Hills region of Louisiana and Mississippi are rich in spruce macrofossils of the extinct species Picea critchfieldii , the one recognized plant extinction of the Late Quaternary. However, the morphology of P. critchfieldii pollen is unknown, presenting a barrier to the interpretation of pollen spectra from the last glacial of North America. To address this issue, we undertook a morphometric study of Picea pollen from Tunica Hills. Morphometric data, together with qualitative observations of pollen morphology using Apotome fluorescence microscopy, indicate that Picea pollen from Tunica Hills is morphologically distinct from the pollen of P. glauca , P. mariana and P. rubens . Measurements of grain length, corpus width and corpus height indicate that Picea pollen from Tunica Hills is larger than the pollen of P. mariana and P. rubens , and is slightly larger than P. glauca pollen. We argue that the morphologically distinctive Tunica Hills Picea pollen was probably produced by the extinct spruce species P. critchfieldii . These morphological differences could be used to identify P. critchfieldii in existing and newly collected pollen records, which would refine its paleoecologic and biogeographic history and clarify the nature and timing of its extinction in the Late Quaternary.

Strategies to evaluate biodegradability: application to chlorinated herbicides - S. Sanchis; A. M. Polo; M. Tobajas; J. J. Rodriguez; A. F. Mohedano (Environmental Science and Pollution Research, 2014)

Fungal endophytes of invasive Phagramites australis populations vary in species composition and fungicide susceptibility - Monika S. Fischer; Rusty J. Rodriguez (Symbiosis, 2013)

CHACO outreach project: the development of a primary health care-based medical genetic service in an Argentinean province - C. Z. Barreiro; M. P. Bidondo; J. A. Garrido; J. Deurloo; E. Acevedo; A. Luna; E. Gutiérrez; C. A. Dellamea; C. Picón; K. Torres; M. F. De Castro; M. V. Torrado; et al. (Journal of Community Genetics, 2013)

Acclimation to Elevated CO2 Increases Constitutive Glucosinolate Levels of Brassica Plants and Affects the Performance of Specialized Herbivores from Contrasting Feeding Guilds - J. Klaiber; S. Dorn; A. J. Najar-Rodriguez (Journal of Chemical Ecology, 2013)

Performance evaluation of a new fourth-generation HIV combination antigen–antibody assay - A. Mühlbacher; H. Schennach; J. van Helden; T. Hebell; G. Pantaleo; P. Bürgisser; C. Cellerai; P. Permpikul; M. I. Rodriguez; A. Eiras; F. Alborino; P. Cunningham; et al. (Medical Microbiology and Immunology, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Zygomycosis Caused by Rhizopus microsporus and Rhizopus oryzae in Madhya Pradesh (M.P.) Central India: A Report of Two Cases - Shesh R. Nawange; S. M. Singh; J. Naidu; S. Jain; T. Nagpal; D. S. Behrani; E. Mellado; J. L. Rodriguez Tudela (Mycopathologia, 2012)

Impact of Earth radiation pressure on GPS position estimates - C. J. Rodriguez-Solano; U. Hugentobler; P. Steigenberger; S. Lutz (Journal of Geodesy, 2012)

Molecular characterization of Staphylococcus aureus from outpatients in the Caribbean reveals the presence of pandemic clones - A.-C. Uhlemann; C. Dumortier; C. Hafer; B. S. Taylor; J. Sánchez E.; C. Rodriguez-Taveras; P. Leon; R. Rojas; C. Olive; F. D. Lowy (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Opacification of Shape Memory Polymer Foam Designed for Treatment of Intracranial Aneurysms - Jennifer N. Rodriguez; Ya-Jen Yu; Matthew W. Miller; Thomas S. Wilson; Jonathan Hartman; Fred J. Clubb; Brandon Gentry; Duncan J. Maitland (Annals of Biomedical Engineering, 2012)

Jatropha adoption: a statistical observational study of factors influencing Malian farmers’ decision to grow Jatropha - M. Basinger; J. Chen; F. Jeffrey-Coker; F. S. Rodriguez-Sanchez; T. Singer; V. Modi (Agroforestry Systems, 2012)

Effect of human-mediated migration and hybridization on the recovery of the American crocodile in Florida (USA) - David Rodriguez; Michael R. J. Forstner; Paul E. Moler; Joseph A. Wasilewski; Michael S. Cherkiss; Llewellyn D. Densmore III (Conservation Genetics, 2011)

Effects of density, climate, and supplementary forage on body mass and pregnancy rates of female red deer in Spain - P. Rodriguez-Hidalgo; C. Gortazar; F. S. Tortosa; C. Rodriguez-Vigal; Y. Fierro; J. Vicente (Oecologia, 2010)

500-year temperature reconstruction in the Mediterranean Basin by means of documentary data and instrumental observations - Dario Camuffo; C. Bertolin; M. Barriendos; F. Dominguez-Castro; C. Cocheo; S. Enzi; M. Sghedoni; A. della Valle; E. Garnier; M.-J. Alcoforado; E. Xoplaki; J. Luterbacher; et al. (Climatic Change, 2010)

Characterization of three sect. Caulopterae species (Baccharis-Asteraceae) inferred from morphoanatomy, polypeptide profiles and spectrophotometry data - M. V. Rodriguez; M. L. Martínez; A. A. Cortadi; A. Bandoni; D. A. Giuliano; S. J. Gattuso; M. A. Gattuso (Plant Systematics and Evolution, 2010)

‘Alternate-goal bias’ in antisaccades and the influence of expectation - Mathias Abegg; Amadeo R. Rodriguez; Hyung Lee; Jason J. S. Barton (Experimental Brain Research, 2010)

Why do humans make antisaccade errors? - Hyung Lee; Mathias Abegg; Amadeo Rodriguez; John Koehn; Jason J. S. Barton (Experimental Brain Research, 2010)

Long‐term transpiration change with rainfall decline in a Mediterranean Quercus ilex forest - J. M. LIMOUSIN; S. RAMBAL; J. M. OURCIVAL; A. ROCHETEAU; R. JOFFRE; R. RODRIGUEZ‐CORTINA (Global Change Biology, 2009)
In the Mediterranean basin, precipitation is expected to decline as a consequence of climate change. The response of a Quercus ilex forest in southern France to such a decline in water availability was studied using a 4‐year throughfall exclusion experiment. Seasonal courses of sap flow and leaf water potential were obtained from 2004 to 2007 and used to characterize tree water relations in a control and a dry treatment. The experiment reduced the average precipitation input to the soil by 29%, and resulted in a 23% reduction in annual transpiration. Soil water potential was significantly lower in the dry treatment only during summer drought, but transpiration was reduced all year round even during well‐watered periods. Despite a tight stomatal control over transpiration, whole‐tree hydraulic conductance was found to be lower in the trees growing in the driest conditions. This reduction in water transport capacity was observed jointly with a reduction in leaf transpiring area. Canopy leaf area decreased by 18% in the dry treatment as a consequence of the throughfall exclusion, which was found to validate the ecohydrological equilibrium theory.

One Hundred Questions of Importance to the Conservation of Global Biological Diversity - W. J. SUTHERLAND; W. M. ADAMS; R. B. ARONSON; R. AVELING; T. M. BLACKBURN; S. BROAD; G. CEBALLOS; I. M. CÔTÉ; R. M. COWLING; G. A. B. DA FONSECA; E. DINERSTEIN; P. J. FERRARO; et al. (Conservation Biology, 2009)
We identified 100 scientific questions that, if answered, would have the greatest impact on conservation practice and policy. Representatives from 21 international organizations, regional sections and working groups of the Society for Conservation Biology, and 12 academics, from all continents except Antarctica, compiled 2291 questions of relevance to conservation of biological diversity worldwide. The questions were gathered from 761 individuals through workshops, email requests, and discussions. Voting by email to short‐list questions, followed by a 2‐day workshop, was used to derive the final list of 100 questions. Most of the final questions were derived through a process of modification and combination as the workshop progressed. The questions are divided into 12 sections: ecosystem functions and services, climate change, technological change, protected areas, ecosystem management and restoration, terrestrial ecosystems, marine ecosystems, freshwater ecosystems, species management, organizational systems and processes, societal context and change, and impacts of conservation interventions. We anticipate that these questions will help identify new directions for researchers and assist funders in directing funds.

Molecular characterization of a foot-and-mouth disease virus containing a 57-nucleotide insertion in the 3′untranslated region - M. E. Piccone; S. Pauszek; J. Pacheco; E. Rieder; E. Kramer; L. L. Rodriguez (Archives of Virology, 2009)

Sex Pheromone of the Scarab Beetle Phyllophaga (Phytalus) georgiana (Horn) - Paul S. Robbins; Satoshi Nojima; Sridhar Polavarapu; Albrecht M. Koppenhöfer; Cesar Rodriguez-Saona; Robert J. Holdcraft; Nancy H. Consolie; Daniel C. Peck; Wendell L. Roelofs (Journal of Chemical Ecology, 2009)

Scintillometer Intercomparison Study—Continued - J. Kleissl; C. J. Watts; J. C. Rodriguez; S. Naif; E. R. Vivoni (Boundary-Layer Meteorology, 2009)

Phytolacca americana from Contaminated and Noncontaminated Soils of South Korea: Effects of Elevated Temperature, CO2 and Simulated Acid Rain on Plant Growth Response - Yong Ok Kim; Rusty J. Rodriguez; Eun Ju Lee; Regina S. Redman (Journal of Chemical Ecology, 2008)

Genetic characterization and molecular epidemiology of foot-and-mouth disease viruses isolated from Afghanistan in 2003–2005 - Kate R. Schumann; Nick J. Knowles; Paul R. Davies; Rebecca J. Midgley; Jean-Francois Valarcher; Abdul Quader Raoufi; Thomas S. McKenna; William Hurtle; James P. Burans; Barbara M. Martin; Luis L. Rodriguez; Tammy R. Beckham (Virus Genes, 2008)

A marker-assisted backcross approach for developing submergence-tolerant rice cultivars - C. N. Neeraja; R. Maghirang-Rodriguez; A. Pamplona; S. Heuer; B. C. Y. Collard; E. M. Septiningsih; G. Vergara; D. Sanchez; K. Xu; A. M. Ismail; D. J. Mackill (Theoretical and Applied Genetics, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Nuclear DNA content of Vitis vinifera cultivars and ploidy level analyses of somatic embryo-derived plants obtained from anther culture - F. Leal; J. Loureiro; E. Rodriguez; M. S. Pais; C. Santos; O. Pinto-Carnide (Plant Cell Reports, 2006)

Successful treatment of septic shock due to pan-resistant Acinetobacter baumannii using combined antimicrobial therapy including tigecycline - F. S. Taccone; H. Rodriguez-Villalobos; D. De Backer; V. De Moor; J. Deviere; J.-L. Vincent; F. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Propensity for paternal inheritance of de novo mutations in Alexander disease - Rong Li; Anne B. Johnson; Gajja S. Salomons; Marjo S. van der Knaap; Diana Rodriguez; Odile Boespflug-Tanguy; J. Rafael Gorospe; James E. Goldman; Albee Messing; Michael Brenner (Human Genetics, 2006)

The effect of headspace renewal in a Temporary Immersion Bioreactor on plantain (Musa AAB) shoot proliferation and quality - S. Roels; C. Noceda; M. Escalona; J. Sandoval; M.J. Canal; R. Rodriguez; P. Debergh (Plant Cell, Tissue and Organ Culture (PCTOC), 2006)

The impacts of climate change in coastal marine systems - Christopher D. G. Harley; A. Randall Hughes; Kristin M. Hultgren; Benjamin G. Miner; Cascade J. B. Sorte; Carol S. Thornber; Laura F. Rodriguez; Lars Tomanek; Susan L. Williams (Ecology Letters, 2006)
Anthropogenically induced global climate change has profound implications for marine ecosystems and the economic and social systems that depend upon them. The relationship between temperature and individual performance is reasonably well understood, and much climate‐related research has focused on potential shifts in distribution and abundance driven directly by temperature. However, recent work has revealed that both abiotic changes and biological responses in the ocean will be substantially more complex. For example, changes in ocean chemistry may be more important than changes in temperature for the performance and survival of many organisms. Ocean circulation, which drives larval transport, will also change, with important consequences for population dynamics. Furthermore, climatic impacts on one or a few ‘leverage species’ may result in sweeping community‐level changes. Finally, synergistic effects between climate and other anthropogenic variables, particularly fishing pressure, will likely exacerbate climate‐induced changes. Efforts to manage and conserve living marine systems in the face of climate change will require improvements to the existing predictive framework. Key directions for future research include identifying key demographic transitions that influence population dynamics, predicting changes in the community‐level impacts of ecologically dominant species, incorporating populations’ ability to evolve (adapt), and understanding the scales over which climate will change and living systems will respond.

Surfactant-Enhanced Desorption of Atrazine and Linuron Residues as Affected by Aging of Herbicides in Soil - M. S. Rodriguez-Cruz; M. J. Sanchez-Martin; M. Sanchez-Camazano (Archives of Environmental Contamination and Toxicology, 2006)

Behavioral alterations in lewis rats following two-day continuous 3-nitropropionic acid administration - J. D. Newcomb; W. D. Brown; A. I. Rodriguez; S. Garbuzova-Davis; S. Saporta; P. R. Sanberg; A. E. Willing (Neurotoxicity Research, 2005)

Optimization of plantain (Musa AAB) micropropagation by temporary immersion system - S. Roels; M. Escalona; I. Cejas; C. Noceda; R. Rodriguez; M. J. Canal; J. Sandoval; P. Debergh (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

Effects of Tropospheric Ozone on Potato Plants Protected by the Antioxidant Diphenylamine (DPA) - J. L. Carrasco-Rodriguez; A. Asensi-Fabado; S. Del Valle-Tascon (Water, Air, & Soil Pollution, 2005)

Development of a citrus genome-wide EST collection and cDNA microarray as resources for genomic studies - J. Forment; J. Gadea; L. Huerta; L. Abizanda; J. Agusti; S. Alamar; E. Alos; F. Andres; R. Arribas; J. P. Beltran; A. Berbel; M. A. Blazquez; et al. (Plant Molecular Biology, 2005)

Environmental Education as a Component of Multidisciplinary Conservation Programs: Lessons from Conservation Initiatives for Critically Endangered Fruit Bats in the Western Indian Ocean - W. J. TREWHELLA; K. M. RODRIGUEZ‐CLARK; N. CORP; A. ENTWISTLE; S. R. T. GARRETT; E. GRANEK; K. L. LENGEL; M. J. RABOUDE; P. F. REASON; B. J. SEWALL (Conservation Biology, 2005)
Pteropus livingstonii , P. voeltzkowi , and P. rodricensis are three critically endangered fruit bats from western Indian Ocean islands for which multidisciplinary conservation programs have been established that include environmental education programs (EEPs). We describe these EEPs in terms of the strategies used to achieve them and evaluate the educational and conservation outcomes and impacts of the programs. Educational outputs (including posters, stickers, videos, lesson plans, and workshops), primarily linking human needs to the ecosystem services provided by bats, were delivered to schools and community groups, and local environmental educators were trained to further develop the EEPs. Outcomes included increased local awareness about the bats and their conservation, training of environmental educators, inclusion of bat conservation and environmental issues in the school curricula, and establishment of community‐based environmental nongovernmental organizations (NGOs). Extensive prior planning, presentations in local languages, distribution of outputs through existing networks of educators, training of local educators, establishment of local environmental NGOs, and local capacity‐building were all associated with these EEPs achieving their goals in the under‐resourced island locations where these bats are found. The EEPs were also important in the development of other components of their respective conservation programs, such as population monitoring programs. Although long‐term conservation impacts, particularly tackling habitat loss, are slow to materialize and social and economic issues need to be addressed, these EEPs have already had important outcomes and have established the foundation for future conservation actions.

The Role of Fungal Symbioses in the Adaptation of Plants to High Stress Environments - Russell J. Rodriguez; Regina S. Redman; Joan M. Henson (Mitigation and Adaptation Strategies for Global Change, 2004)

Transgenic Rice as a Vehicle for the Production of the Industrial Enzyme Transglutaminase - M.I. Claparols; L. Bassie; B. Miro; S. Del Duca; J. Rodriguez-Montesinos; P. Christou; D. Serafini-Fracassini; T. Capell (Transgenic Research, 2004)

Experimental Study of the Formation of Chlorination By-Products in Potable Water of Quebec City, Canada - M. J. Rodriguez; M. Huard; J.-B. Srodes (Bulletin of Environmental Contamination and Toxicology, 2004)

A comparative study of the expression of monoamine oxidase-A and -B mRNA and protein in non-CNS human tissues - S. D. Sivasubramaniam; C. C. Finch; M. J. Rodriguez; N. Mahy; E. E. Billett (Cell and Tissue Research, 2003)

Comparative analysis of superfamilies of NBS-encoding disease resistance gene analogs in cultivated and wild apple species - S.-Y. Lee; J.-S. Seo; M. Rodriguez-Lanetty; D.-H. Lee (Molecular Genetics and Genomics, 2003)

Calcium, vitamin D, dairy products, and risk of colorectal cancer in the Cancer Prevention Study II Nutrition Cohort (United States) - Marjorie L. McCullough; Andrea S. Robertson; Carmen Rodriguez; Eric J. Jacobs; Ann Chao; Carolyn Jonas; Eugenia E. Calle; Walter C. Willett; Michael J. Thun (Cancer Causes & Control, 2003)

The reliability of immunohistochemistry as a prescreening method for the diagnosis of hereditary nonpolyposis colorectal cancer (HNPCC) – Results of an international collaborative study - Wolfram Müller; Lawrence J. Burgart; Ruth Krause-Paulus; Stephen N. Thibodeau; M. Almeida; T. Brocker Edmonston; C. R. Boland; C. Sutter; J. R. Jass; A. Lindblom; J. Lubinski; K. MacDermot; et al. (Familial Cancer, 2001)

Physical and chemical processes in the application of CA and/or fumigation - Cecilia V. De Dios; Maria Finesa A. Cosico; Ma. Elvira M. Martinez; D. D. Julian; I. V. Dator; R. L. Tiongson; J. van S. Graver; S. Pratt; C. Reed; Sylvia Allen; G. N. Mbata; T. W. Phillips; et al. (Phytoparasitica, 2001)

Plant species diversity as a driver of early succession in abandoned fields: a multi-site approach - W. H. Van der Putten; S. R. Mortimer; K. Hedlund; C. Van Dijk; V. K. Brown; J. Lepä; C. Rodriguez-Barrueco; J. Roy; T. A. Diaz Len; D. Gormsen; G. W. Korthals; S. Lavorel; et al. (Oecologia, 2000)

Patterns of inpatient surgeries for the top four cancers in the United States, National Hospital Discharge Survey, 1988–95 - Phyllis A. Wingo; Jodie L. Guest; LaMar McGinnis; Daniel S. Miller; Carmen Rodriguez; Cheryll J. Cardinez; Brian Morrow; Michael J. Thun (Cancer Causes & Control, 2000)

The correlation of the gene csoS2 of the carboxysome operon with two polypeptides of the carboxysome in Thiobacillus neapolitanus - S. H. Baker; S. C. Lorbach; M. Rodriguez-Buey; Donna S. Williams; Henry C. Aldrich; J. M. Shively (Archives of Microbiology, 1999)

A statistical approach to study the dynamics of micropropagation rates, using banana ( Musa spp.) as an example - B. M. J. Mendes; S. B. Filippi; C. G. B. Demétrio; A. P. M. Rodriguez (Plant Cell Reports, 1999)

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Neurological and functional effects of short-term exposure to hand-arm vibration - J. Malchaire; L. S. Rodriguez Diaz; A. Piette; F. Gonçalves Amaral; D. de Schaetzen (International Archives of Occupational and Environmental Health, 1998)

Spatial and temporal patterns of annual precipitation variability over the Iberian Peninsula - C. Rodriguez-Puebla; A. H. Encinas; S. Nieto; J. Garmendia (International Journal of Climatology, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Reproductive Toxicology of 3,3',4,4'-Tetrachlorobiphenyl in Mice - J. Rodriguez; S. D. Kholkute; W. R. Dukelow (Bulletin of Environmental Contamination and Toxicology, 1997)

Beta interferon production in primed and unprimed cells infected with human cytomegalovirus - J. E. Rodriguez; T. R. Loepfe; N. S. Swack (Archives of Virology, 1987)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1981)

Influenza A viruses: Combinations of hemagglutinin and neuraminidase subtypes isolated from animals and other sources - V. S. Hinshaw; R. G. Webster; R. J. Rodriguez (Archives of Virology, 1979)

Fetal infection of the baboon(Papio cynocephalus) with lymphocytic choriomeningitis virus - R. Ackermann; S. S. Kalter; R. L. Heberling; B. McCullough; J. Eichberg; A. R. Rodriguez (Archives of Virology, 1979)

Clinical, virological, and pathological features of herpesvirus SA8 infection in conventional and gnotobiotic infant baboons(Papio cynocephalus) - J. W. Eichberg; B. McCullough; S. S. Kalter; D. E. Thor; A. R. Rodriguez (Archives of Virology, 1976)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)